Kota Gresik Sebagai Kota Santri “Implikasi Sebagai City Branding” - Nora Faridatin (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2016)
Identity is part part of self concept of someone which involves the values, emotion, eangagement level, caring and also a sense of pride to its members. The identity of someone or society group in particular places to be vulnerable toward every changing around it. Phenomenon of city branding and it implication toward society appears at identity of society in Gresik city. Method which is used in this research is descriptive-interpretative in which data are gathering through observation, interview, document study, and interpretative analysis using theory. The theory of public space theory from Jurgen Habermas is used to explain the identity of society in Gresik city which has city branding as Santri city. This research is done in two district, they are district Manyar and district Gresik. The result of this research, first Gresik city pasca-industrialization shows new identity as industry city, but still committed to their previous identity as Santri city. Second,  there are social changes as the impact of city branding, such as structure aspects, culture and social interaction.